Analisis Lingkungan Internal Dan Eksternal Pada Bisnis Advertising CV. Nabila Advertising - Sari Mariahma Nova Sipayung (Musamus Journal of Business & Management, 2022)
This study aims to examine, describe and analyze the internal and external environment in the advertising business of CV. Nabila Advertising. This type of research is qualitative research with a descriptive approach using primary and secondary data sources. This study focused on internal factors with SWOT analysis (Strength, Weakness, Opportunities, Threat) and external factors with PEST (Political, Economic, Social, Technology) analysis. Data collection techniques are in-depth interviews, observation, and documentation. From the SWOT analysis, the resulting SWOT quadrant position is in quadrant II, which means the company has strength but faces external threats. The strategy that must be applied is to use strength to take advantage of long-term opportunities with a diversification strategy (product/service). Meanwhile, from the PEST analysis, we get a big picture of external influences that are important and affect the company so that the company can be better prepared to face the threats and dangers faced.